The Correlation Between Calcium and Iron Intake with Dysmenorrhea in Female Adolescents in SMA Negeri 1 Ambarawa - Maria Magdalena Meilina Rahmawati; Sugeng Maryanto; Purbowati (UNIVERSITAS NGUDI WALUYO, 2021)
Dysmenorrhea is pain in the stomach that comes from uterine cramps and occurs during menstruation. Menstrual pain or dysmenorrhea can have an impact on learning activities in adolescents. The incidence of dysmenorrhea in Central Java reaches 56%. Calcium and iron intake are factors that can affect the incidence of dysmenorrhea. The research objective was to determine the correlation between calcium and iron intake and the incidence of dysmenorrhea in female adolescents at SMA Negeri 1 Ambarawa. This study is a descriptive correlation study with a cross sectional approach. The population was 501 students of SMA Negeri 1 Ambarawa. There were 87 subjects taken by proportional random sampling. Collecting data using UPAT (Universal Pain Assessment Tool) and FFQ (Food Frequency Questionnaire). The data were analyzed using kendals’tau control test (α = 0.05). Research results female adolescent calcium intake is 92.0% less, 6.9% good, and 1.1% more. The iron intake of female adolescent was 96.6% less, 2.3% good, and 1.1% more. The incidence of dysmenorrhea in female adolescent was 44.8% mild pain, 28.7% moderate pain, 8.0% severe pain, 5.7% very severe pain, and 12.6% no pain. There is a correlation between calcium intake and the incidence of dysmenorrhea (p = 0.008). There is a correlation between iron intake and the incidence of dysmenorrhea (p = 0.005).